Liquid crystal lenticular lens array with extended aperture by using gradient refractive index compensation. Issue 3 (19th February 2021) - Li, Rui; Chu, Fan; Tian, Li-Lan; Gu, Xiao-Qing; Zhou, Xiang-Yu; Wang, Qiong-Hua
ABSTRACT: A liquid crystal (LC) lenticular lens array with extended aperture by using gradient refractive index compensation is proposed. For the traditional LC lenticular lens, the phase distribution curve gradually flattens with the increase of the aperture size. To enlarge the aperture of the traditional LC lenticular lens, two LC cells with corresponding patterned electrodes are stacked together. The aperture of the proposed LC lenticular lens is expanded to 760 μm as a result of the gradient refractive index compensation of the bottom LC cell, and the phase distribution is lens-like. As the driving voltage increases from 0 V to 7.5 V, the focal length of the proposed LC lenticular lens decreases from ∞ to 6.67 mm. The focal length is reduced compared with that of the traditional LC lenticular lens. GRAPHICAL ABSTRACT: uf0001